A MODEL OF EFFECTIVE ADMINISTRATION DEVELOPMENT BASED ON GOOD GOVERNANCE FOR PRIMARY SCHOOLS UNDER OFFICE OF PRIMARY EDUCATION SERVICE AREA - Siribhaddo (Chamsaithong), PhramahaVinai; Chamnisast, Booncherd; Chaisuk, Peeravat (Journal of Educational Review Faculty of Education in MCU, 2020)
This research paper aimed to propose a model of effective administration development based on good governance for primary schools under the Office of Primary Education Service Area. Mixed methods research with three steps was designed which were: Step 1: the state of administration based on good governance for primary schools under the Office of Primary Education Service Area, data were collected from 400 samples using questionnaires. Step 2: developed the model by interviewing 24 key informants, and Step 3: validated a model by focus group discussions with 10 experts and proposed it. Research results indicated that a model of effective administration development based on good governance for primary schools under the Office of Primary Education Service Area consisted of 1) principles, 2) objectives, 3) operational procedures, 4) operational processes. It was the process of conducting school management development in four areas: (1) academic administration, (2) personnel management, (3) budget management, and (4) general administration. The main good governance was integrated with the principle of good governance and society consisted of (1) rule of law, (2) moral code, (3) transparency principle, (4) accountability principle, (5) participatory principle, and (6) value principle.